Practical issues in developing a smart surface irrigation system with real-time simulation of furrow advance - Shahidian, Shakib (2014)
Automation of surface irrigation can be an economic and ecological way of increasing global food production. In this work a fully automated cablegation system is evaluated that adapts the application time and depth to the actual infiltration rate of the soil in real-time. The system calculates the infiltration equation from advance times in a control furrow and then simulates irrigation in every furrow of the field, establishing the optimum application time for each furrow. The methodology was evaluated in a field organized in contour terraces with furrows of various lengths in order to evaluate practical issues affecting the performance of the system. The results confirm the temporal variability in soil infiltration, and the need for real-time determination of the infiltration equation. The evolution of furrow geometry through the season did not have an important impact on the results of the simulations. The length of the furrow considered for calculating the Kostiakov equation influences the parameters of the equation. Automation with real-time feedback can result in important savings in water and labour and can produce irrigation events with more than 90% application efficiency. Nevertheless, the results also indicate that there are practical limits to what can possibly be achieved with automation and real-time feedback from the field